Teladan Rasuli dan Implikasinya dalam Hidup Menggereja 1 Korintus 9:1-27 - Rumondang Lumban Gaol (Jurnal Teologi Cultivation, 2021)
AbstractApostles are servants sent by Christ who are tasked with witnessing about Christ and teaching in the fellowship or community of Christ's followers so that they are seen as pillars of teachers and have a very important role in ministry. Therefore, an Apostle must be an example or role model that should be imitated by the congregation or society because they are very influential figures. The purpose of this study is to examine how the Apostle Paul set himself as an example in his ministry and fulfills his apostolic calling through the text of 1 Corinthians 9: 1-27 and its implications in church life, especially for church servants today. The research method used in this paper is a literature study (library). Based on the study in the text of 1 Corinthians 9: 1-27, several examples of the Apostle Paul's ministry were found, including, not claiming rights for himself and refusing to use his rights as the main thing; prioritize the task of preaching the gospel; use his freedom to win many people and be able to control himself / self-control. Keywords: Servants of God; Apostle Paul; Exemplary AbstrakRasul adalah pelayan yang diutus oleh Kristus yang bertugas memberi kesaksian tentang Kristus serta pengajaran dalam persekutuan atau komunitas pengikut Kristus sehingga  mereka dipandang sebagai soko guru dan memiliki peran yang sangat penting dalam pelayanan. Oleh sebab itu seorang Rasul haruslah menjadi contoh atau teladan  yang patut ditiru oleh jemaat atau masyarakat karena mereka adalah figur yang sangat berpengaruh. Tujuan penelitian ini adalah mengkaji bagaimana Rasul Paulus menjadikan dirinya sendiri sebagai teladan dalam tugas pelayanannya dan memenuhi panggilan kerasulannya melalui teks 1 Korintus 9: 1-27 dan implikasinya dalam hidup menggereja khususnya bagi pelayan gereja saat ini. Metode penelitian yang digunakan dalam tulisan ini adalah studi literatur (kepustakaan). Berdasarkan kajian dalam teks 1 Korintus 9: 1-27 ditemukan beberapa teladan pelayanan Rasul Paulus diantaranya, tidak menuntut hak untuk dirinya sendiri dan menolak mempergunakan haknya sebagai yang utama; mengutamakan tugas pemberitaan Injil; mempergunakan kebebasannya untuk memenangkan banyak orang dan mampu menguasai diri/pengendalian diri. Kata Kunci: Pelayan Tuhan; Rasul Paulus; Teladan